Avaliação da resistência ao cisalhamento de um solo tropical não saturado - Fagundes, Lucas Savio [UNESP] (2014)
Tropical soils have peculiar characteristics and behavior considering its geology and soil-genesis typical of tropical regions. In those regions, there are long periods of rainy and dry seasons, which cause variation of water content and, consequently, on soil suction. The value of soil shear strengh is directly related to the variation of suction and studying their correlation helps to better understand the behavior of unsaturated tropical soils. This research studied the shear strength of an unsaturated tropical soil obtained by suction-controlled triaxial compression tests (consolidated-drained) on undisturbed and compacted soil samples. The method proposed by Vilar (2007) was used adjust the tests results, so the shear strength could be predicted. The set of results obtained for the soil was used to model the soil behavior, considering the Barcelona Basic Model - BBM (Alonso et al., 1990) e as modificações sugeridas por Wheler et. al. (2002). As curvas de retenção de água do solo foram obtidas para contribuir com a caracterização do solo. Por fim, ensaios com Bender Elements instalados na câmara triaxial foram realizados. Nos resultados e análises, foi evidenciado que a compactação e o aumento de sucção geram acréscimo de resistência. A coesão do solo indeformado variou de forma linear com a sucção. Para o solo compactado a variação foi não linear e o ajuste sugerido por Vilar (2007) foi satisfatório. A modelagem pelo BBM e as sugestões de Wheeler et. al. (2002) mostraram-se adequadas para o solo indeformado. Os ensaios com Bender Elements mostraram que acréscimos na tensão confinante provocou um aumento não linear do módulo de cisalhamento máximo, tanto para o solo saturado quanto para o solo com sucção controlada de 100 kPa